Teaching chemistry in the cloud: The preparation of future teachers for 21st century learning - Suthida Chamrat (2019)
© 2019 Author(s). This paper describes classroom action research (n=14) aimed to prepare future chemistry teachers who are undergraduate students in the Chemistry major of the Faculty of Education at Chiang Mai University, Thailand. Face-to- face teaching was combined with learning chemistry based on Cloud Technology Integrated Learning to develop the students' conceptualization of chemistry and, also, to promote 21st century learning in Thailand. Cloud technology, associated with Web Application such as Google Drive, Google Form and YouTube, have become increasingly valued learning tools of the digital age, especially for students from low income families where the cost of traditional textbooks, paper copies of journal articles and other materials may be prohibitive. This study focused on the scope of the potential of Cloud Technologies for future educators to develop an understanding of how they could be incorporated into the instruction techniques. Carefully designed usage and integration into the classroom, these technologies encouraged students' active engagement, collaboration, and participation in their learning, facilitate group work, and facilitated the teachers' abilities to elicit students' conceptions for formative assessment. "Just in time" feedback for the students was employed to improve the students understanding of chemistry concepts. Using the collected data on the cloud, the teacher helped students to conceptualize and learn new concepts in a proper way. Data pertaining to student Google Forms use and activities was collected. The data was analyzed qualitatively to understand the effects of using Cloud Technology Integrated Learning with chemistry instruction, on students' motivation for learning and using chemistry conceptualization. The findings identify the potential benefits to learning and teaching from Cloud Technology Integrated Learning environment.